Wide band gap kesterite absorbers for thin film solar cells: potential and challenges for their deployment in tandem devices. Issue 9 (24th June 2019) - Vermang, Bart; Brammertz, Guy; Meuris, Marc; Schnabel, Thomas; Ahlswede, Erik; Choubrac, Leo; Harel, Sylvie; Cardinaud, Christophe; Arzel, Ludovic; Barreau, Nicolas; van Deelen, Joop; Bolt, Pieter-Jan; et al.
Abstract : This study describes the potential and challenges involved with the use of wide bandgap kesterite absorbers in tandem solar cells. Abstract : This work reports on developments in the field of wide band gap Cu2 ZnXY4 (with X = Sn, Si or Ge, and Y = S, Se) kesterite thin film solar cells. An overview on recent developments and the current understanding of wide band gap kesterite absorber layers, alternative buffer layers, and suitable transparent back contacts is presented. Cu2 ZnGe(S, Se)4 absorbers with absorber band gaps up to 1.7 eV have been successfully developed and integrated into solar cells. Combining a CdS buffer layer prepared by an optimized chemical bath deposition process with a 1.36 eV band gap absorber resulted in a record Cu2 ZnGeSe4 cell efficiency of 7.6%, while the highest open-circuit voltage of 730 mV could be obtained for a 1.54 eV band gap absorber and a Zn(O, S) buffer layer. Employing InZnO x or TiO2 protective top layers on SnO2 :In transparent back contacts yields 85–90% of the solar cell performance of reference cells (with Mo back contact). These advances show the potential as well as the challenges of wide band gap kesterites for future applications in high-efficiency and low-cost tandem photovoltaic devices.